Isolation and characterization of Escherichia coliO157:H7 from ground beef cattle in Lima-Peru - Méndez, Carmen R. (2013)
The aim of the study was to isolate and characterize E. coli O157: H7 from fresh ground beef obtained in different food markets. 195 samples were analyzed, for isolation and enumeration of E. coliwas used most probable number technique using multiple tubes, for the isolation and characterization of E. coliO157: H7 selective enrichment and biochemical analysis, characteristic colonies were confirmed serologically. To determine the presence of shigatoxin (stx1, stx2) and intimin (eaeA) was done with multiplex real time PCR and for enterohemolysin the hemolysis test. The 87.18% of the samples were positive for E. coliand 77.95% had a count greater than or equal to 50 NMP/g. Were obtained 3 (1.54%) strains of E. coliO157: H7, one stx1 +/stx2 +/eaeA - and enterohemolysin -, one stx1 +/stx2 -/eaeA + and enterohemolysin - and the other stx1 -/stx2 -/eaeA - and enterohemolysin +. Also obtained 4 (2.05%) strains of E. coliO157 non H7, no virulence factors presented. The study found that the risk potential E. coliO157: H7 affecting the population of Lima